IEEE Power Engineering Society Summer Meeting,
DOI: 10.1109/pess.2002.1043379
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous machine stability analysis using an efficient time domain methodology: unbalanced operation analysis

Abstract: This paper describes a methodology for the efficient stability analysis of the synchronous machine. The state space phase coordinates model of the synchronous machine incorporates the effects of time-varying and inter-spatial harmonic inductances. The dynamics of the synchronous machine are represented by a set of Ordinary Differential Equations (ODEs). The machine behaviour is analyzed under severe unbalanced operation conditions. The level of detail and accuracy obtained with the machine model in phase coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…2, the transient responses produced by all models coincide and converge to the reference solutions. This clearly demonstrates that these models are all equivalent and predict the unbalanced operations with acceptable accuracy for the given time step, which is contrary to the conclusions made in [24]- [28].…”
Section: A Small Time-step Studycontrasting
confidence: 78%
See 4 more Smart Citations
“…2, the transient responses produced by all models coincide and converge to the reference solutions. This clearly demonstrates that these models are all equivalent and predict the unbalanced operations with acceptable accuracy for the given time step, which is contrary to the conclusions made in [24]- [28].…”
Section: A Small Time-step Studycontrasting
confidence: 78%
“…The authors of [24]- [26] suggested that the different simulation results obtained by the and PD models may be caused by "different data based on their frames of reference" [24] and listed the machine's internal circuit data and test data in the Appendices of [24], [25]. However, these two sets of data are equivalent, as is shown in [21].…”
Section: B Impact Of Parameter Conversion Methodsmentioning
confidence: 99%
See 3 more Smart Citations